Space life matter : the coming of age of Indian science - Pulakkat, Hari (Hachette Book Publishing India, 2021)
How do you build a scientifically and technologically strong modern nation with limited means and resources? Indian scientists faced this challenge seven decades ago when the country became independent and confronted a world rapidly advancing in science and technology. In the years that followed, they battled poor funding and archaic regulations to build India's science infrastructure from scratch. This fascinating narrative captures the story of the struggles and triumphs of these leaders of science and the world-class institutions they founded. From the cosmic-ray experiments at the Kolar Gold Fields to ISRO's stunning space observatory built under severe constraints, from the construction of one of the world's largest radio telescopes in Ooty to the development of structural biology at IISc and, most recently, the significant contributions of the country's scientific institutions towards tackling a global pandemic. Space. Life. Matter. brings to readers the path-breaking advances made by India's scientists to original research and what they mean to the nation's progress. Deeply informed, enlightening and inspiring, this singular, comprehensive account of the pride of place that Indian science occupies in the world is essential reading for all -- front flap.